CONSCIENCE KEAGAMAAN: BIMBINGAN CONSCIENCE KEAGAMAAN PADA MASYARAKAT PEDALAMAN - Ashari Ismail .; Idham Irwansyah Idrus (Universitas Negeri Makassar, 2022)
Abstract. The effort to form a dignified and religious rural community is not only dependent on the government and scholars, but also academics. This guidance, which can be applied to the hinterland community of Tandara, Kaili Luwu, South Sulawesi is an attempt to raise religious awareness, so that the target community has a firm religious awareness, avoids syncrtism or religious bias. The results of the guidance show that the target community has the power of conscience and the effort to be aware, practice religion, in accordance with the religious guidance they believe in. Keywords: Guidance, Conscience, Religion